PENGARUH EKUITAS MEREK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA GERAI STARBUCKS DI BALI - Agustini, Ni Putu Evi; Suasana, I Gst. A. Kt. Gd. (Buletin Studi Ekonomi, 2020)
The purpose of this study was to determine the effect of brand equity, price and service quality on purchasing decisions. The study was conducted on Starbucks consumers in Bali with a sample of 145 respondents using a nonprobability sampling method, namely purposive sampling. Data collection using a questionnaire taken from several Starbucks outlets in Bali. The analysis technique used is descriptive analysis and inferential analysis, namely: multiple regression analysis. The analysis found that brand equity has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, and service quality has a positive and significant effect on purchasing decisions. Other results found that simultaneously brand equity, price and service quality variables also have a positive and significant effect on purchasing decisions. Based on the results of the study found, Starbucks has reached a good level of brand equity, the most important thing is to maintain and improve overall performance. Starbucks is expected to maintain the quality of service to consumers so as to increase sales.